Penggunaan Shopee Paylater Dalam Ekonomi Islam - Friska Fadhila; Abd. Malik; Khairiyani (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to explore how people in the Islamic economy feel about the Shopee app's PayLater feature. And to get a breakdown of how Shopee PayLater is being utilised. The methodology of this study is qualitative. This research uses observation, interviews, and documentation to gather information. While data visualisation and reduction are used for analysis. According to the findings of this research, Shopee users can benefit from the convenience of Shopee PayLater's on-time payment options by taking advantage of the company's bailout funds. Shopee PayLater continues to impose unnecessary costs on its customers by charging interest on past due balances and other fees with every purchase. The Qardh and Prohibition of Transactions in the Islamic economy state that Shopee PayLater is not permitted because it contains elements that are detrimental to the user, so the app's use is prohibited if it is banned in the Islamic economy.